How to win friends and influence people - Carnegie, Dale; Semy, Haitenlo (Mumbai, India wilco international house, 2023)
Published during the Great Depression and equally valuable during booming economies and difficult times - Dale Carnegie's valuable, time tested, rock solid advice has carried millions of people up the ladder of success in their personal and business lives. This ground breaking book introduces us to simple yet life changing concepts in order to get what you want, improve what you have and make any situation work for you!
Over 6 million copies sold
Keywords: Interpersonal relations; Self-actualization (Psychology); Success